The Political Network Governance of Indonesia's Low-Carbon Transition: A CIMO-Based Review - Fajar Alamsyah; Romy Hermawan (IJBAMS: International Journal of Business Accounting Management Social Science, 2026)
Despite international climate commitments, Indonesia's low-carbon policy implementation faces barriers stemming from state-business nexuses. This study analyzes actor networks impeding green economy governance. Employing a Systematic Literature Review (SLR) integrated with the CIMO (Context-Intervention-Mechanism-Outcome) framework, 16 studies were synthesized using NVivo. Results reveal a fragmented state apparatus contrasting with dominant fossil fuel interests entrenched in patronage networks. Quantitative data indicates significant power asymmetries, with 36.8 million hectares allocated to corporations versus 3.1 million hectares to communities. Regulatory capture is evident, exemplified by the 0% royalty clause in the Omnibus Law. Consequently, implementation gaps persist; although presidential commitments aim to reduce coal, 14 GW of new coal capacity was ratified until 2030. Distributive injustices are severe, with an estimated 6,500–15,700 annual premature deaths due to coal emissions. The system exhibits carbon lock-in, projecting coal dominance until 2050. The study concludes that green regulatory stagnation results from historically constituted state-business power configurations rather than technical incapacity. Addressing informal ties between state elites and business interests is crucial. Recommendations include transparent governance designs to minimize fossil fuel dominance and accelerate progress toward the 2060 Net Zero Emission target.